Direct measurement of electrostatic interactions between poly(methyl methacrylate) microspheres with optical laser tweezers. Issue 40 (24th September 2019) - Choi, Kyu Hwan; Kang, Dong Woo; Kim, Kyung Hak; Kim, Jiwon; Lee, Youngbok; Im, Sang Hyuk; Park, Bum Jun
Abstract : Strong electrostatic repulsive forces between PMMA particles in CHB/decane mixtures were directly measured with optical laser tweezers. Abstract : In this study, we measured the force of electrostatic interactions between poly(methyl methacrylate) (PMMA) particles dispersed in organic solvent mixtures of cyclohexyl bromide (CHB) and n -decane. Optical laser tweezers were employed to directly measure interactive forces between paired PMMA particles in a CHB medium that contained n -decane in various volume ratios. CHB, having a moderate dielectric constant, provided an environment with a high charge storage capacity. The addition of n -decane lowered the effective refractive index of the medium, which increased the optical trapping efficiency. We also fabricated microscope flow cells with a commonly used UV-curable adhesive and quantified the effects of dissolved adhesive compounds through interactive force measurements and nuclear magnetic resonance analysis. In addition, we studied the impact of CHB dissociation into H + and Br − ions, which could screen electrostatic interactions.